HUBUNGAN POSTUR KERJA DENGAN KEJADIAN MYALGIA PADA PETANI DI KECAMATAN BUNGAYA KABUPATEN GOWA - Putri Azis; Asrijun Juhanto; Rahmawati Rahmawati (UNM Environmental Journals, 2022)
Complaints of muscle pain are symptoms in the body that are often suffered by humans which are characterized by the appearance of pain or aching, heaviness, stiffness in the muscles. Work that is carried out for a long time and is accompanied by the use of inappropriate body postures and can pose a risk of interference with the muscles in doing work, including standing, sitting, squatting, bending, walking which can result in myalgia. The purpose of this study was to determine the relationship between work posture and the incidence of myalgia in farmers in Bungaya District, Gowa Regency. This research is a quantitative study with a cross sectional study approach. The total population in the study was 101 farmers. The sampling technique in this study used the Slovin Formula with a total sample of 51 samples selected. Data were analyzed by chi-square test α (0.05). The research results obtained statistically showed that there was a relationship between knowledge (p-values = 0.027) and length of work duration (p-value = 0.000) with Myalgia Incidence, while age (p-values = 0.514) and work posture (p-values = 0.351) there is no relationship with the incidence of myalgia. The conclusion of the research results shows that there is a relationship between knowledge and length of work with the incidence of myalgia, and there is no relationship between age and work posture with the incidence of myalgia. It is hoped that the public can pay attention to the position when working, especially the duration of work when working no more than 8 hours/day.